Bibliometric Analysis of Mathematics Learning Video using VOSviewer. How the Trend and What Next? - Muntazhimah, Muntazhimah (FKIP Universitas Lampung, 2022)
Bibliometric Analysis of Mathematics Learning Video Using VOSviewer. How the Trend and What Next?. Mathematics learning video is one of the audio-visual media used to increase students’ interests, motivations, and achievements in mathematics learning. Methods: This study is a bibliographic analysis of mathematics learning videos, which has not yet previously been conducted. Objectives: This study addresses research trends and future research opportunities on mathematics learning videos. Findings: 300 article metadata on mathematics learning videos were extracted by Publish or Perish (PoP) software from the Google Scholar database. Those articles have been published until 2022. From 1579 terms, 32 related terms were obtained, and only 25 were verified. Network, overlay, and density visualizations were generated using VOSviewer software. Conclusion: Finally, this study provides suggestions for possible future research on the mathematics learning videos. Keywords: bibliometric analysis, mathematics learning video, vosviewer.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202236